Successful fresh formulation CD19 CAR-T cell therapy for GAD65 antibody-mediated cerebellar ataxia. A Case Report - Vaisvilas, Mantas; Cernauskiene, Skirmante; Petrosian, David; Giedraitiene, Natasa; Stoskus, Mindaugas; Griskevicius, Laimonas (Frontiers in Immunology, 2026)
BackgroundChimeric antigen receptor T (CAR-T) cell therapy is an effective treatment for treatment-refractory hematological disorders with an acceptable safety profile. In contrast, preliminary reports suggest good efficacy for treatment-refractory autoimmune disorders, including autoimmune nervous system disease, but their safety profile is largely unknown.ObjectiveTo describe the first case of glutamic acid decarboxylase-65 (GAD65) antibody-mediated cerebellar ataxia (CA) successfully treated with CD19 CAR-T cells.ResultsA 33-year-old male was diagnosed with GAD65 antibody mediated CA in 2023. Despite treatment with Rituximab and Cyclophosphamide, the patient’s condition worsened with new-onset recurrent falls and increasing vertigo. Ambulation was maintained. CD19 CAR-T cells at a dose of 1 × 106 cells per kilogram of body weight were infused after administration of standard lymphodepleting chemotherapy, resulting in a good serological response with reduction of GAD65 serum titers by 95% at day +90, significant clinical improvement in ataxia at day +30 and no evidence of disease progression at day +270 clinically, radiologically and laboratory-wise. The toxicity was limited to cytokine release syndrome grade 1.DiscussionThe favorable clinical response observed in our patient, along with other reports demonstrating preliminary efficacy and limited toxicity, supports further study of CD19 CAR-T cell therapy in GAD65 neurological disorders.